A case of traumatic myiasis in a white stork (ciconia ciconia) caused by lucilia sericata (diptera: calliphoridae) - Mehmet Yaman; Aykut Zerek; Şerife Akküçük (Eurasian Journal of Veterinary Sciences)
A stork was brought to the Mustafa Kemal University, Faculty of Veterinary Clinics with the complaint of injury. On the examination, larvae were observed open humerus fracture on the left wing. Larvae were identified depending on the morphological characters of the anterior spiracles, posterior spiracles and cephalo-pharyngeal skeleton. The results of microscopic examination of the larvae were identified as the third stage larvae of Lucilia sericata. According to the literature information, traumatic myiasis cases were rarely observed in white storks. A case of traumatic myiasis in a white stork caused by L. sericata reported in Hatay.